Arabidopsis leaf hydraulic conductance is regulated by xylem sap pH, controlled, in turn, by a P‐type H+‐ATPase of vascular bundle sheath cells. (17th April 2021) - Grunwald, Yael; Wigoda, Noa; Sade, Nir; Yaaran, Adi; Torne, Tanmayee; Gosa, Sanbon Chaka; Moran, Nava; Moshelion, Menachem
SUMMARY: The leaf vascular bundle sheath cells (BSCs) that tightly envelop the leaf veins, are a selective and dynamic barrier to xylem sap water and solutes radially entering the mesophyll cells. Under normal conditions, xylem sap pH below 6 is presumably important for driving and regulating the transmembranal solute transport. Having discovered recently a differentially high expression of a BSC proton pump, AHA2, we now test the hypothesis that it regulates the xylem sap pH and leaf radial water fluxes. We monitored the xylem sap pH in the veins of detached leaves of wild‐type Arabidopsis, AHA mutants and aha2 mutants complemented with AHA2 gene solely in BSCs. We tested an AHA inhibitor (vanadate) and stimulator (fusicoccin), and different pH buffers. We monitored their impact on the xylem sap pH and the leaf hydraulic conductance ( K leaf ), and the effect of pH on the water osmotic permeability ( P f ) of isolated BSCs protoplasts. We found that AHA2 is necessary for xylem sap acidification, and in turn, for elevating K leaf . Conversely, AHA2 knockdown, which alkalinized the xylem sap, or, buffering its pH to 7.5, reduced K leaf, and elevating external pH to 7.5 decreased the BSCs P f . All these showed a causative link between AHA2 activity in BSCs and leaf radial hydraulic water conductance. Significance Statement: We reveal a mechanism regulating the leaf hydraulic conductance in response to xylem sap pH. The pH regulation is enabled by H + ‐ATPase (AHA2) localized in the Arabidopsis bundle sheath cells enwrapping the leaf vasculature. While guard cells regulate loss of water from the leaf, bundle sheath cells act in series, independently, regulating water influx into the leaf. Our findings provide an understanding of the plant water‐balance regulation.